Group social capital and the employment prospects of refugee women who experience domestic violence. (2nd October 2022) - Caspersz, Donella; Casado, Renata; Kaplanian, Carol; Fozdar, Farida; Baldassar, Loretta
ABSTRACT: This paper offers research insights on how refugee women who experience domestic violence develop employment prospects. Guided by social capital theory and the concept of group social capital, the paper uses a qualitative approach to identify intrapersonal and interpersonal processes in a group intervention that assist women members to adjust their cognitive reasoning about their domestic violence experience and engage in behaviours that potentially enhance their employment prospects. The paper contributes to understanding how group processes can foster small wins that may enhance the employment prospects of this vulnerable group.